Neodymium-iron-boron magnet, nickel-cobalt-phosphorus-molybdenum alloy coating, preparation method and application thereof

By using nickel-cobalt-phosphorus-molybdenum alloy coating on the surface of neodymium-ferroboron magnets and introducing nickel, cobalt, phosphorus and molybdenum elements, the problem of insufficient corrosion resistance of existing neodymium-ferroboron magnets is solved, and higher resistance is achieved Corrosion and high-temperature magnetic resistance reduce production costs.

CN119419026APending Publication Date: 2025-02-11TIANJIN SANHUAN LUCKY NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411365804.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing surface anti-corrosion treatment methods of neodymium iron boron magnets have problems such as insufficient corrosion resistance, high cost and large environmental pollution.

Method used

Using nickel, cobalt, phosphorus and molybdenum alloy plating, by introducing nickel, cobalt, phosphorus and molybdenum elements into the plating, the coating is formed with high density and low porosity, which improves the corrosion resistance of neodymium iron boron magnets and reduces the nickel content to improve the Resistance to high temperature and magnetization.

Benefits of technology

It significantly improves the corrosion resistance and high-temperature magnetic reduction performance of neodymium iron boron magnets, while reducing production costs and achieving higher density and lower porosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419026A_ABST
    Figure CN119419026A_ABST
Patent Text Reader

Abstract

The invention provides a neodymium-iron-boron magnet, a nickel-cobalt-phosphorus-molybdenum alloy coating, a preparation method and application thereof. The nickel-cobalt-phosphorus-molybdenum alloy coating comprises nickel, cobalt, phosphorus and molybdenum. Wherein the mass percentage of nickel to molybdenum is (5: 1)-(20: 1). The nickel-cobalt-phosphorus-molybdenum alloy coating provided by the invention has extremely high binding force with a neodymium-iron-boron substrate, and the coating is low in internal stress, low in porosity and high in density, so that the corrosion resistance and the humidity and heat resistance of the neodymium-iron-boron magnet are effectively improved; and the electroplating process suitable for the electroplating solution is stable, the surface of a plating layer is smooth, and the electroplating solution can be better suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of neodymium iron boron magnets, and in particular to a neodymium iron boron magnet and a nickel-cobalt-phosphorus-molybdenum alloy coating thereof, a preparation method and use thereof. Background Art

[0002] NdFeB magnets are widely used in wind power, motors, smart consumer electronics and other industries due to their excellent comprehensive magnetic properties. However, NdFeB magnets have a multi-phase structure with large electrochemical differences between phases, which can easily cause electrochemical corrosion, making NdFeB magnets very susceptible to rust and corrosion, so surface anti-corrosion treatment is required.

[0003] At present, conventional surface anti-corrosion treatment methods can be divided into: electroplating, chemical plating, chemical conversion film, electrophoresis and physical vapor deposition, etc., to obtain metal or alloy film layers, polymer film layers, chemical conversion film layers and composite film layers.

[0004] The electroplating coating on the surface of conventional NdFeB magnets is generally a single layer of nickel, nickel-copper, nickel-copper-nickel, etc. In order to improve the corrosion resistance, a chemical nickel layer is generally added to the surface of the NdFeB magnet. However, the chemical nickel layer has a short life, high cost, and serious environmental pollution.

[0005] Therefore, it is necessary to develop new surface coatings for NdFeB magnets to improve corrosion resistance and reduce environmental pollution. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a neodymium iron boron magnet and a nickel-cobalt-phosphorus-molybdenum alloy coating, a preparation method and a use thereof. By simultaneously introducing nickel, cobalt, phosphorus and molybdenum elements into the coating, not only a coating with high density and low porosity can be obtained, thereby improving the corrosion resistance of the neodymium iron boron magnet, but also the nickel content in the alloy coating can be reduced, thereby improving the high temperature demagnetization resistance of the neodymium iron boron magnet.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a nickel-cobalt-phosphorus-molybdenum alloy coating of a neodymium-iron-boron magnet, wherein the composition of the nickel-cobalt-phosphorus-molybdenum alloy coating includes nickel, cobalt, phosphorus and molybdenum; wherein the nickel content: molybdenum content is 5:1 to 20:1 in terms of mass percentage.

[0009] Since the electroplated nickel layer generally has many pores on the surface of the coating and has poor corrosion resistance, the present invention adds phosphorus to the electroplated layer to seal the pores, thereby improving the corrosion resistance of the coating. When the high corrosion resistance requirement is not met, the general method is to simply increase the thickness of the coating. However, as the thickness of the coating increases, the content of metal nickel in the coating increases, resulting in a decrease in the high-temperature anti-demagnetization ability of the magnet. The present invention can replace part of the metal nickel by introducing metal molybdenum, thereby ensuring that the magnet meets the high corrosion resistance requirement and reducing the adverse effects of metal nickel on the magnetic properties of the NdFeB magnet.

[0010] The addition of molybdenum in the present invention can partially replace nickel, and the addition of an appropriate amount of molybdenum can serve as a coordination metal, so that the alloy coating has excellent wear resistance, high thermal stability, and hot hardness. By controlling the mass ratio of nickel content: molybdenum content within the above range, the content of each component can be combined and coordinated to comprehensively improve the magnetic properties of the nickel-cobalt-phosphorus-molybdenum alloy coating.

[0011] In the present invention, the nickel content: molybdenum content is 5:1 to 20:1 by mass percentage, for example, it can be 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, 10:1, 10.5:1, 11:1, 11.5:1, 12:1, 13:1, 13.5:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1, etc.

[0012] Preferably, the nickel content:cobalt content is 4:1 to 16:1, calculated by mass percentage, for example, it can be 4:1, 4.5:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 or 16:1, etc.

[0013] In the nickel-cobalt-phosphorus-molybdenum alloy coating of the present invention, the ratio of the nickel content to the cobalt content is preferably controlled within the above range, wherein if the Co content is too low, the coating hardness is low, the coating is relatively soft, and the coating mechanical properties are relatively poor; if the Co content is too high, the coating hardness increases while the internal stress increases, which increases the brittleness of the film layer and easily generates cracks. In addition, a high Co content will reduce the remanence of the magnet; and the nickel content is limited to be less than or equal to 80wt%, which can ensure the nickel-cobalt-phosphorus-molybdenum alloy phase and avoid the situation where the main phase is nickel. If the nickel content is too low, the Co content needs to be increased accordingly. A high Co content is likely to lead to a higher remanence, affecting the magnetic properties of the magnet.

[0014] Preferably, the ratio of nickel content to phosphorus content in the nickel-cobalt-phosphorus-molybdenum alloy coating is 4:1 to 25:1, for example, it can be 4:1, 5:1, 6:1, 7:1, 8:1, 10:1, 12:1, 15:1, 18:1, 20:1, 22:1, 23:1 or 25:1.

[0015] Preferably, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 10 μm, for example, it can be 3 μm, 3.8 μm, 4.6 μm, 5 μm, 5.4 μm, 6 μm, 6.2 μm, 6.9 μm, 7.7 μm, 8.5 μm, 9.3 μm or 10 μm.

[0016] The thickness range of the nickel-cobalt-phosphorus-molybdenum alloy coating in the present invention is relatively large. When the nickel-cobalt-phosphorus-molybdenum alloy coating is used alone, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 6 to 10 μm; or, when the nickel-cobalt-phosphorus-molybdenum alloy coating is used in combination with other coatings, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 5 μm.

[0017] The present invention has no special restrictions on other coatings, and other coating materials known to those skilled in the art can be used in combination with the nickel-cobalt-phosphorus-molybdenum alloy coating, such as epoxy / physical deposition film layer / nickel coating layer and / or nickel-containing alloy coating layer. The present invention has no special restrictions on the arrangement order of the nickel-cobalt-phosphorus-molybdenum alloy coating used in combination with other coatings, and the nickel-cobalt-phosphorus-molybdenum alloy coating can be arranged close to the NdFeB magnet, or at the position farthest from the NdFeB magnet, or between at least two other coatings.

[0018] The nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet described in the first aspect of the present invention can be formed by electroplating with the electroplating solution of the NdFeB magnet described in the second aspect, or can be formed by other methods. It is preferably formed by electroplating with the electroplating solution of the NdFeB magnet described in the second aspect of the present invention, and has higher density and lower porosity, and has a higher degree of bonding with the NdFeB magnet.

[0019] In a second aspect, the present invention provides an electroplating solution for a neodymium iron boron magnet, the electroplating solution comprising:

[0020]

[0021]

[0022] In the electroplating solution of the present invention, nickel salt, cobalt salt, molybdate and hypophosphite are used to provide nickel, cobalt, molybdenum and phosphorus elements to form a nickel-cobalt-phosphorus-molybdenum alloy coating. When the content of hypophosphite is low, the Ni-P bonding effect cannot be effectively achieved; when the content of cobalt salt is low, the coating hardness is low, the coating is soft, and the coating mechanical properties are poor; when the content of cobalt salt is high, the coating hardness increases and the internal stress increases, which increases the brittleness of the film layer and is prone to cracks. In addition, a large amount of Co content will reduce the remanence of the magnet. The addition of molybdenum salt can partially replace nickel salt, and the addition of an appropriate amount of molybdenum salt can serve as a coordination metal, so that the alloy coating has excellent wear resistance, high thermal stability, and hot hardness.

[0023] The electroplating solution of the present invention includes 100-200 g / L of nickel salt, for example, it can be 100 g / L, 112 g / L, 123 g / L, 130 g / L, 134 g / L, 145 g / L, 156 g / L, 167 g / L, 178 g / L, 180 g / L, 189 g / L or 200 g / L.

[0024] The cobalt salt is 10 to 30 g / L, for example, it can be 10 g / L, 13 g / L, 15 g / L, 17 g / L, 19 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L.

[0025] Molybdate 8-30 g / L, for example, can be 8 g / L, 10 g / L, 13 g / L, 15 g / L, 17 g / L, 19 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L or 30 g / L.

[0026] Hypophosphite 10-20 g / L, for example, can be 10 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L.

[0027] Preferably, the electroplating solution further comprises:

[0028]

[0029] The complexing agent in the present invention can increase the cathode polarization effect, make the coating crystal thinner, and significantly increase the dispersibility and covering ability of the plating solution. The surfactant, preferably an anionic surfactant, can reduce the surface tension of the plating solution and reduce the occurrence of quality problems such as pinholes. The softener can reduce the brittleness of the coating, improve the toughness of the coating and enhance the bonding strength between the coating and the NdFeB magnet. The stabilizer can improve the stability of the plating solution, prevent the precipitation of metal ions, improve the uniformity of the components of the plating solution during the electroplating process, and can stabilize the dispersed state of the metal particles, thereby improving the uniformity of the components in the coating.

[0030] The present invention preferably sets the composition of each substance within the above range, which can significantly obtain a nickel-cobalt-phosphorus-molybdenum alloy coating with uniform composition and excellent surface quality.

[0031] The complexing agent in the present invention is 180-220 g / L, for example, it can be 180 g / L, 185 g / L, 189 g / L, 194 g / L, 198 g / L, 203 g / L, 207 g / L, 212 g / L, 216 g / L or 220 g / L.

[0032] The surfactant is 0.2 to 0.5 g / L, for example, it can be 0.2 g / L, 0.24 g / L, 0.27 g / L, 0.3 g / L, 0.34 g / L, 0.37 g / L, 0.4 g / L, 0.44 g / L, 0.47 g / L or 0.5 g / L.

[0033] The softener is 8 to 15 g / L, for example, it can be 8 g / L, 8.8 g / L, 9.6 g / L, 10.4 g / L, 11.2 g / L, 11.9 g / L, 12.7 g / L, 13.5 g / L, 14.3 g / L or 15 g / L.

[0034] The stabilizer is 30-45 g / L, for example, it can be 30 g / L, 32 g / L, 34 g / L, 35 g / L, 37 g / L, 39 g / L, 40 g / L, 42 g / L, 44 g / L or 45 g / L.

[0035] Preferably, the nickel salt comprises nickel sulfate.

[0036] Preferably, the cobalt salt comprises cobalt sulfate.

[0037] Preferably, the molybdate comprises sodium molybdate.

[0038] Preferably, the hypophosphite comprises sodium hypophosphite.

[0039] Preferably, the complexing agent comprises any one or a combination of at least two of trisodium citrate, aminoacetic acid or malonic acid, wherein typical but non-limiting combinations are a combination of trisodium citrate and aminoacetic acid, a combination of trisodium citrate and malonic acid, a combination of malonic acid and aminoacetic acid, preferably trisodium citrate.

[0040] Preferably, the surfactant comprises any one of sodium dodecyl sulfate, sodium n-octyl sulfate or sodium dodecylbenzene sulfonate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of sodium dodecyl sulfate and sodium n-octyl sulfate, a combination of sodium dodecylbenzene sulfonate and sodium n-octyl sulfate, and a combination of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0041] The present invention selects the above-mentioned surfactant to reduce the surface tension of the solution and reduce the occurrence of quality problems such as pinholes. Preferably, the softener includes benzenesulfonamide and / or saccharin sodium.

[0042] It is worth noting that the concentration of benzenesulfonamide in the softener when used alone is 11-12 g / L, for example, it can be 11 g / L, 11.2 g / L, 11.3 g / L, 11.4 g / L, 11.5 g / L, 11.6 g / L, 11.7 g / L, 11.8 g / L, 11.9 g / L or 12 g / L, or the concentration of saccharin sodium when used alone is 13-14 g / L, for example, it can be 13 g / L, 13.2 g / L, 13.3 g / L, 13.4 g / L, 13.5 g / L, 13.6 g / L, 13.7 g / L, 13.8 g / L, 13.9 g / L or 14 g / L, etc.

[0043] Preferably, the mass ratio of benzenesulfonamide to saccharin sodium in the softener is 1:2 to 1:0.5, for example, it can be 1:2, 1:1.5, 1:1.2, 1:1, 1:0.65, 1:0.7, 1:0.8 or 1:0.5, etc.

[0044] Preferably, the stabilizer comprises boric acid and / or sodium acetate.

[0045] It is worth noting that the concentration of boric acid in the stabilizer when used alone is 35-40 g / L, for example, it can be 35 g / L, 35.6 g / L, 36.2 g / L, 36.7 g / L, 37.3 g / L, 37.8 g / L, 38.4 g / L, 38.9 g / L, 39.5 g / L or 40 g / L, etc.; or the concentration of sodium acetate when used alone is 35-38 g / L, for example, it can be 35 g / L, 35.4 g / L, 35.7 g / L, 36 g / L, 36.4 g / L, 36.7 g / L, 37 g / L, 37.4 g / L, 37.7 g / L or 38 g / L, etc.

[0046] Preferably, the mass ratio of boric acid to sodium acetate in the stabilizer is 5:1 to 1.5:1, for example, it can be 5:1, 4.5:1, 4:1, 3.5:1, 3:1, 2.8:1, 2.5:1, 2.0:1, 1.8:1 or 1.5:1, etc.

[0047] Preferably, the electroplating solution further comprises: a conductive salt.

[0048] The present invention further includes a conductive salt in the electroplating solution. The conductive salt mainly provides free charged ions to improve the conductivity of the electroplating solution, and the anions in the conductive salt do not have a complexing effect on the main salt metal ions.

[0049] Preferably, the conductive salt comprises any one of sodium sulfate, sodium chloride or ammonium chloride or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of sodium sulfate and sodium chloride, a combination of ammonium chloride and sodium chloride, and a combination of sodium sulfate and ammonium chloride.

[0050] Preferably, the concentration of the conductive salt in the electroplating solution is 20-35 g / L, for example, it can be 20 g / L, 22 g / L, 23 g / L, 24 g / L, 25 g / L, 28 g / L, 30 g / L, 32 g / L, 33 g / L, 34 g / L or 35 g / L, etc.

[0051] Preferably, the concentration of the conductive salt in the plating solution when sodium sulfate is used alone is 25 g / L to 35 g / L, for example, it can be 25 g / L, 27 g / L, 29 g / L, 30 g / L, 32 g / L, 34 g / L, 35 g / L, 37 g / L, 39 g / L or 40 g / L.

[0052] Sodium chloride is generally used in combination with other conductive salts. When the electroplating solution contains sodium chloride, its concentration is 10g / L to 20g / L, for example, it can be 10g / L, 12g / L, 13g / L, 14g / L, 15g / L, 16g / L, 17g / L, 18g / L, 19g / L or 20g / L.

[0053] Ammonium chloride is generally used in combination with other conductive salts. When ammonium chloride is contained in the plating solution, its concentration is 5g / L to 15g / L, for example, it can be 5g / L, 7g / L, 8g / L, 9g / L, 10g / L, 11g / L, 12g / L, 13g / L, 14g / L or 15g / L.

[0054] The solvent of the electroplating solution in the present invention is water, generally deionized water.

[0055] In a third aspect, the present invention provides a method for preparing a nickel-cobalt-phosphorus-molybdenum alloy coating of a neodymium-iron-boron magnet, the preparation method comprising: placing the neodymium-iron-boron magnet in the electroplating solution described in the second aspect for electroplating to obtain a neodymium-iron-boron magnet containing a nickel-cobalt-phosphorus-molybdenum alloy coating.

[0056] Preferably, the temperature of the plating solution in the electroplating is 45-60°C, for example, it can be 45°C, 47°C, 49°C, 50°C, 52°C, 54°C, 55°C, 57°C, 59°C or 60°C.

[0057] In the present invention, the temperature of the plating solution during the electroplating process is preferably within the above range, which can better control the electroplating reaction rate, thereby better regulating the size of the crystals and improving the corrosion resistance of the coating. After the temperature increases, the cathode polarization decreases and the coating crystals become coarser.

[0058] The temperature of the electroplating solution of the present invention is preferably within the above range, which can better match the composition of the electroplating solution and achieve excellent electroplating effect.

[0059] Preferably, the pH of the plating solution in the electroplating is 4.0-6.5, for example, it can be 4.0, 4.3, 4.6, 4.9, 5.2, 5.4, 5.7, 6, 6.3 or 6.5.

[0060] In the present invention, the pH of the plating solution is preferably within the above range. On the one hand, it can ensure the stability of ions in the plating solution and prevent precipitation. On the other hand, it can avoid the problem of loose layers forming at corners due to too high pH. On the third hand, it can avoid the problem of hydrogen precipitation caused by too low pH, thereby forming defects on the surface of the film layer.

[0061] The pH of the electroplating solution in the present invention is adjusted by sulfuric acid solution.

[0062] Preferably, the stirring speed in the plating solution during the electroplating is 300-400 r / min, for example, it can be 300 r / min, 312 r / min, 323 r / min, 334 r / min, 345 r / min, 356 r / min, 367 r / min, 378 r / min, 389 r / min or 400 r / min.

[0063] Preferably, the cathode current density in the electroplating is 0.8 to 1.4 A·dm -2 , for example, it can be 0.8A·dm -2 、0.87A·dm -2 、0.94A·dm -2 、1A·dm -2 、1.07A·dm -2 、1.14A·dm -2 , 1.2A·dm -2 、1.27A·dm -2 、1.34A·dm -2 or 1.4A·dm -2 wait.

[0064] The method also includes: pre-treating the NdFeB magnet before the electroplating.

[0065] Preferably, the pre-treatment comprises: grinding and chamfering, degreasing, pickling and activation treatment of the NdFeB magnet in sequence.

[0066] Preferably, the chamfering grinding time is 4 to 10 hours, for example, it can be 4 hours, 4.7 hours, 5.4 hours, 6 hours, 6.7 hours, 7.4 hours, 8 hours, 8.7 hours, 9.4 hours or 10 hours.

[0067] Preferably, the abrasive for grinding and chamfering includes any one of triangular abrasive, trapezoidal abrasive or circular abrasive, or a combination of at least two of them, wherein a typical but non-limiting combination is a combination of triangular abrasive and trapezoidal abrasive, a combination of circular abrasive and trapezoidal abrasive, and a combination of triangular abrasive and circular abrasive.

[0068] Preferably, the degreasing time is 20 to 40 min, for example, it can be 20 min, 23 min, 25 min, 27 min, 29 min, 32 min, 34 min, 36 min, 38 min or 40 min.

[0069] Preferably, the degreasing solution comprises any one of sodium hydroxide, sodium carbonate, sodium bicarbonate or potassium hydroxide or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of sodium hydroxide and sodium carbonate, a combination of sodium bicarbonate and sodium carbonate, a combination of sodium hydroxide and sodium bicarbonate, and a combination of potassium hydroxide and sodium carbonate.

[0070] Preferably, the pickling time is 10 to 120 s, for example, it can be 10 s, 23 s, 35 s, 47 s, 59 s, 72 s, 84 s, 96 s, 108 s or 120 s.

[0071] Preferably, the pickling solution comprises any one of hydrochloric acid, nitric acid or sulfuric acid or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of hydrochloric acid and nitric acid, a combination of sulfuric acid and nitric acid, and a combination of hydrochloric acid and sulfuric acid.

[0072] Preferably, the activation treatment time is 10 to 60 s, for example, it can be 10 s, 16 s, 22 s, 27 s, 33 s, 38 s, 44 s, 49 s, 55 s or 60 s.

[0073] Preferably, the activation solution for the activation treatment comprises 3-5% sulfuric acid, for example, 3%, 3.3%, 3.5%, 3.7%, 3.9%, 4.2%, 4.4%, 4.6%, 4.8% or 5%, etc.; and 3-6% ammonium bifluoride, for example, 3%, 3.4%, 3.7%, 4%, 4.4%, 4.7%, 5%, 5.4%, 5.7% or 6%, etc.

[0074] In a fourth aspect, the present invention provides a neodymium iron boron magnet, comprising the nickel-cobalt-phosphorus-molybdenum alloy coating of the neodymium iron boron magnet described in the first aspect; and / or the preparation method of the neodymium iron boron magnet comprises the preparation method of the nickel-cobalt-phosphorus-molybdenum alloy coating of the neodymium iron boron magnet described in the second aspect.

[0075] Preferably, the NdFeB magnet comprises a magnet body and a coating located on the surface of the magnet body.

[0076] Preferably, the coating comprises a nickel-cobalt-phosphorus-molybdenum alloy coating.

[0077] Preferably, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 10 μm, for example, it can be 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, etc.

[0078] Optionally, when the coating contains only a nickel-cobalt-phosphorus-molybdenum alloy coating, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 6 to 10 μm; or, the coating also includes a second coating, and the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 5 μm.

[0079] Preferably, the second coating layer comprises any one of an epoxy film layer, a physically deposited film layer, a nickel plated layer or a nickel-containing alloy plated layer, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of an epoxy film layer and a physically deposited film layer, a combination of a nickel plated layer and a physically deposited film layer, a combination of an epoxy film layer and a nickel plated layer, a combination of a nickel-containing alloy plated layer and a physically deposited film layer, and a combination of a nickel-containing alloy plated layer and an epoxy film layer.

[0080] In a fifth aspect, the present invention provides a use of the NdFeB magnet described in the fourth aspect in the fields of wind power, motors or smart consumer electronics.

[0081] The NdFeB magnet provided by the present invention has an excellent anti-corrosion effect in the fields of wind power, motors or smart consumer electronics due to the nickel-cobalt-phosphorus-molybdenum alloy coating, excellent performance and broad application prospects.

[0082] Compared with the prior art, the present invention has at least the following beneficial effects:

[0083] (1) The nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet provided by the present invention adds phosphorus to the electroplating layer, which can play a role in sealing the pores. Furthermore, molybdenum is added to the electroplating layer. The introduction of metal molybdenum can replace part of the metal nickel, thereby ensuring that the magnet meets the high corrosion protection requirements while reducing the adverse effects of metal nickel on the magnetic properties of the NdFeB magnet.

[0084] (2) The electroplating process applicable to the electroplating solution provided by the present invention is stable, the surface of the coating is smooth, and it can be better applied to industrial production;

[0085] (3) The nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet provided by the present invention has extremely high bonding strength with the NdFeB substrate, and the coating has low internal stress, low porosity, and high density, which effectively improves the corrosion resistance and moisture and heat resistance of the NdFeB magnet;

[0086] (4) The nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet provided by the present invention has extremely strong corrosion resistance. Under the premise of meeting the corrosion resistance conditions, the thickness of the alloy coating can be greatly reduced, thereby reducing the production cost; under preferred conditions, the nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet provided by the present invention can achieve a salt spray test result of more than 120h, a PCT test result of more than 130h, and a high-temperature demagnetization performance of less than 0.6%. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] Figure 1 This is a metallographic micrograph of the nickel-cobalt-phosphorus-molybdenum alloy coating provided in Application Example 1 of the present invention, magnified 10 times.

[0088] Figure 2 This is a metallographic micrograph of the nickel-cobalt-phosphorus-molybdenum alloy coating provided in comparative example 4 of the present invention, magnified 10 times. DETAILED DESCRIPTION

[0089] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0090] Example 1

[0091] This embodiment provides an electroplating solution, the electroplating solution comprising:

[0092]

[0093]

[0094] Example 2

[0095] This embodiment provides an electroplating solution, the electroplating solution comprising:

[0096]

[0097] Example 3

[0098] This embodiment provides an electroplating solution. Except that the concentration of cobalt sulfate in the electroplating solution is 8 g / L, the rest is the same as that in Embodiment 1, and will not be described again.

[0099] Example 4

[0100] This embodiment provides an electroplating solution. Except that the concentration of cobalt sulfate in the electroplating solution is 35 g / L, the rest is the same as that in Embodiment 1, and will not be described again.

[0101] Comparative Example 1

[0102] This comparative example provides an electroplating solution, which is the same as Example 1 except that sodium hypophosphite is not added, and will not be described again.

[0103] Comparative Example 2

[0104] This comparative example provides an electroplating solution, which is the same as Example 1 except that cobalt sulfate is not added, and will not be described again.

[0105] Comparative Example 3

[0106] This comparative example provides an electroplating solution, which is the same as Example 1 except that the concentration of sodium molybdate is 5 g / L, and will not be described again.

[0107] Comparative Example 4

[0108] This comparative example provides an electroplating solution, which is the same as Example 1 except that the concentration of sodium molybdate is 35 g / L, and will not be described again.

[0109] Application Example 1

[0110] This application example provides a neodymium iron boron magnet, and a method for preparing a nickel-cobalt-phosphorus-molybdenum alloy coating of the neodymium iron boron magnet comprises:

[0111] The NdFeB magnet (with a specification of 20mm*10mm*5mm) is firstly subjected to triangular abrasive with a diameter of 10mm and a vibration mill vibration frequency of 50Hz for grinding and chamfering for 5h. After the chamfering is completed, the NdFeB permanent magnet is ultrasonically cleaned and dried; then, degreasing is performed with a sodium hydroxide solution for 30min, ultrasonically cleaned after degreasing, pickled with dilute nitric acid for 100s, washed with three-stage countercurrent water after the pickling is completed, and activated with an activation solution (4% sulfuric acid and 5% ammonium bifluoride) for 50s, ultrasonically cleaned after the activation is completed, and the pre-treated NdFeB magnet is obtained;

[0112] The pre-treated NdFeB magnet was placed in the electroplating solution provided in Example 1 for electroplating (hanging plating), the temperature of the electroplating solution was 50°C, the pH was 5.5, the stirring speed in the electroplating solution was 350 r / min, the cathode current density was 1.0 A·dm -2 The electroplating time is 70 min, and a NdFeB magnet containing a nickel-cobalt-phosphorus-molybdenum alloy coating is obtained.

[0113] Application Example 2

[0114] This application example provides a neodymium iron boron magnet, and a method for preparing a nickel-cobalt-phosphorus-molybdenum alloy coating of the neodymium iron boron magnet comprises:

[0115] The NdFeB magnet (with a specification of 20mm*10mm*5mm) is firstly treated with triangular abrasive and trapezoidal abrasive (mass ratio 1:1), the abrasive specification diameter = 10mm, the vibration frequency of the vibration mill is set to 50Hz, and the grinding and chamfering are performed for 4h. After the chamfering is completed, the NdFeB permanent magnet is ultrasonically cleaned and dried; then, a sodium hydroxide solution is used for degreasing for 40min, and after the degreasing is completed, it is ultrasonically cleaned, and then pickled with dilute hydrochloric acid for 10s, and after the pickling is completed, it is washed with three-stage countercurrent water, and an activation solution (5% sulfuric acid and 3% ammonium bifluoride) is used for activation treatment for 10s, and after the activation is completed, it is ultrasonically cleaned to obtain a pre-treated NdFeB magnet;

[0116] The pre-treated NdFeB magnet was placed in the electroplating solution provided in Example 2 for electroplating (roller plating). The temperature of the electroplating solution was 60° C., the pH was 5.0, the stirring speed in the electroplating solution was 300 r / min, and the cathode current density was 1.4 A·dm -2 The electroplating time is 60 min, and a NdFeB magnet containing a nickel-cobalt-phosphorus-molybdenum alloy coating is obtained.

[0117] Application Examples 3 to 4 and Application Comparative Examples 1 to 4 provide a nickel-cobalt-phosphorus-molybdenum alloy coating of a neodymium iron boron magnet. The nickel-cobalt-phosphorus-molybdenum alloy coating of the neodymium iron boron magnet is the same as Application Example 1 except that the plating solutions in Examples 3 to 4 and Comparative Examples 1 to 4 are used respectively, and are not described again here.

[0118] Application Example 5

[0119] This application example provides a neodymium iron boron magnet. The preparation method of the nickel-cobalt-phosphorus-molybdenum alloy coating of the neodymium iron boron magnet controls the electroplating time to 30 minutes on the basis of Application Example 1 to obtain a 4μm thick nickel-cobalt-phosphorus-molybdenum alloy coating, and sprays epoxy on the basis of the nickel-cobalt-phosphorus-molybdenum alloy coating. The spraying pressure is 0.6mPa, the spraying time is 120s, the spray gun distance is 10cm, and the total thickness after spraying epoxy is 6μm.

[0120] Application Example 6

[0121] The pretreatment is the same as in Application Example 1. First, the nickel layer is electroplated. The composition of the electroplating solution is: 140g / L nickel sulfate, 12g / L nickel chloride, 25g / L boric acid, 0.8g / L sodium dodecyl sulfate, and the solvent is deionized water. The roller plating method is adopted. The temperature of the electroplating solution is 55°C, the pH is 3.4, the stirring speed in the electroplating solution is 300r / min, and the cathode current density is 2.2A·dm -2, the electroplating time is 60min, the thickness of the nickel layer is 3.5μm; then the copper layer is electroplated, the electroplating solution composition is: copper pyrophosphate 65g / L, potassium pyrophosphate 310g / L, diammonium hydrogen citrate 30g / L, the roller plating method, the electroplating solution temperature is 35℃, the pH is 8.5, the stirring speed in the electroplating solution is 300r / min, and the cathode current density is 1.2A·dm -2 , the electroplating time is 60min, and the thickness of the copper layer is 5μm; finally, the electroplating solution composition and electroplating process in Example 1 are adopted, and the other processes are the same as those in Application Example 1, and the electroplating time in Application Example 1 is shortened to 40min, and the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 5μm.

[0122] Application Comparative Example 5

[0123] This application comparative example provides a method for preparing nickel-copper-nickel-nickel of a neodymium-iron-boron magnet, the preparation method comprising the following steps:

[0124] The first layer of nickel: nickel sulfamate: 255g / L, nickel chloride: 20g / L, boric acid 35g / L, the plating solution temperature is 38°C, the pH value is 4.0, and the cathode current density is 3.5A·dm -2 .

[0125] The second layer of copper: the main components of the plating solution are copper pyrophosphate 70g / L, potassium pyrophosphate 280g / L, diammonium hydrogen citrate 22g / L, the plating solution temperature is 35℃, the pH value is 8.5, and the cathode current density is 1.2A·dm -2 .

[0126] Nickel layer 3: Nickel sulfamate: 400 g / L, boric acid 35 g / L, plating solution temperature 38°C, pH 4.0, cathode current density 5.0 A·dm -2 .

[0127] Nickel layer 4: nickel sulfamate: 300 g / L, nickel chloride: 25 g / L, boric acid 38 g / L, additives (specific substances are thiourea, coumarin) 0.2 g / L, plating solution temperature is 358 ° C, pH value is 4.0, cathode current density is 3.0 A·dm -2 . Test methods and conditions:

[0128] 1) Salt spray test conditions: temperature 35±2℃, 50±5g / LNaCl, splash speed 1~2ml / 80cm 2 h, pH: 6.5~7.2.

[0129] 2) PCT experimental conditions are: temperature: 120±2°C, 100% RH, absolute pressure: 0.1985 MPa.

[0130] 3) Element content test: Use ICP component analysis instrument for testing.

[0131] 4) Coating thickness test: Measure the average value of multiple groups (such as three groups) of thickness at different sampling areas of the workpiece to be tested.

[0132] 5) High temperature demagnetization performance test of magnet: the test temperature is 150°C, high temperature demagnetization rate = [(normal temperature magnetic flux) - (magnet flux after high temperature for a period of time returns to normal temperature)) / (magnet flux at normal temperature) * 100%)]. The microscopic morphology of application example 1 and application comparative example 4 are as follows: Figures 1-2 As shown in the figure, it can be seen that the pores between the alloy particles in the film layer formed in Application Example 1 are smaller, and the film layer is denser.

[0133] The test results of the above application examples and application comparison examples are shown in Table 1.

[0134] Table 1

[0135]

[0136] In Table 1, “ / ” indicates that there is no relevant data.

[0137] From Table 1, we can see the following points:

[0138] (1) It can be seen from the comprehensive application examples 1 to 2 that the NdFeB magnet containing the nickel-cobalt-phosphorus-molybdenum alloy coating provided by the present invention can achieve a salt spray test result of more than 120 hours, a PCT test result of more than 130 hours, and a high-temperature demagnetization performance of less than 0.6%, indicating that the nickel-cobalt-phosphorus-molybdenum alloy coating provided by the present invention can improve the corrosion resistance of the NdFeB magnet and can reduce the nickel content in the alloy coating, thereby improving the high-temperature demagnetization performance of the NdFeB magnet.

[0139] (2) It can be seen from the comprehensive application examples 1 and application examples 3 to 4 that the content of cobalt sulfate in application example 1 is 15 g / L, and the ratio of nickel content to cobalt content in the final nickel-cobalt-phosphorus-molybdenum alloy coating is 8.2:1. Compared with the cobalt sulfate content in application examples 3 to 4 being 8 g / L and 35 g / L respectively, and the ratio of nickel content to cobalt content in the final nickel-cobalt-phosphorus-molybdenum alloy coating being 17.2:1 and 4.6:1 respectively, the salt spray test result in application example 1 is up to 120 h, while the salt spray test results in application examples 3 to 4 are only 80 h and 100 h respectively. The PCT experimental results are also significantly shortened compared with application example 1. This shows that the present invention preferably controls the content of cobalt sulfate within a specific range, so as to control the nickel content: cobalt content in the nickel-cobalt-phosphorus-molybdenum alloy coating within a reasonable range, and finally can improve the corrosion resistance of the NdFeB magnet;

[0140] (3) It can be seen from the comprehensive application examples 5 to 6 that the nickel-cobalt-phosphorus-molybdenum alloy coating in the NdFeB magnet provided by the present invention can be combined with other coatings and has better performance;

[0141] (4) Comprehensive application of comparative examples 1 to 2 shows that in the application of comparative example 1, sodium hypophosphite is not added, and the alloy coating formed does not contain P, resulting in a salt spray test result of only 60h, a PCT test result of only 100h, and a high-temperature demagnetization performance of only 1.0%, resulting in a significant decrease in the performance of the alloy coating; in the application of comparative example 2, cobalt sulfate is not added, resulting in the coating containing no cobalt, and the final salt spray test result of only 90h, the PCT test result of only 100h, and a high-temperature demagnetization performance of 1.2%, which shows that the present invention can better improve the corrosion resistance and magnetic properties of NdFeB magnets through the combination of various components;

[0142] (5) It can be seen from the comprehensive application of Comparative Examples 3 to 4 that the concentration of sodium molybdate has a significant effect on the performance of the nickel-cobalt-phosphorus-molybdenum alloy coating. The present invention controls the concentration of sodium molybdate within a reasonable range, which can significantly improve the high-temperature anti-demagnetization ability and corrosion resistance of the NdFeB magnet;

[0143] (6) It can be seen from the comprehensive application example 1 and the application comparison example 5 that the comprehensive magnetic properties and high-temperature magnetic properties of the traditional nickel-copper-nickel-nickel coating are far inferior to those of the nickel-cobalt-phosphorus-molybdenum alloy coating in the application example 1 of the present invention. This shows that the nickel-cobalt-phosphorus-molybdenum alloy coating provided by the present invention has extremely strong corrosion resistance and high-temperature anti-demagnetization ability.

[0144] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A nickel-cobalt-phosphorus-molybdenum alloy coating of a neodymium-iron-boron magnet, characterized in that: The composition of the nickel-cobalt-phosphorus-molybdenum alloy coating includes nickel, cobalt, phosphorus and molybdenum; wherein, in terms of mass percentage, the nickel content: molybdenum content is 5:1 to 20:

1.

2. The nickel-cobalt-phosphorus-molybdenum alloy coating according to claim 1, characterized in that: Calculated by mass percentage, the nickel content: cobalt content is 4:1 to 16:1; And / or, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 10 μm.

3. A plating solution for NdFeB magnets, characterized in that: The electroplating solution comprises:

4. The electroplating solution according to claim 3, characterized in that The electroplating solution also includes: Preferably, the nickel salt comprises nickel sulfate; Preferably, the cobalt salt comprises cobalt sulfate; Preferably, the molybdate comprises sodium molybdate; Preferably, the hypophosphite comprises sodium hypophosphite.

5. The electroplating solution according to claim 3 or 4, characterized in that: The softener includes benzenesulfonamide and / or saccharin sodium; Preferably, the mass ratio of benzenesulfonamide to saccharin sodium in the softener is 1:2 to 1:0.5; Preferably, the stabilizer comprises boric acid and / or sodium acetate; Preferably, the mass ratio of boric acid to sodium acetate in the stabilizer is 5:1 to 1.5:

1.

6. The electroplating solution according to any one of claims 3 to 5, characterized in that: The electroplating solution also includes: a conductive salt; Preferably, the conductive salt includes any one of sodium sulfate, sodium chloride or ammonium chloride, or a combination of at least two thereof; Preferably, the concentration of the conductive salt in the electroplating solution is 20-35 g / L.

7. A method for preparing a nickel-cobalt-phosphorus-molybdenum alloy coating of a neodymium-iron-boron magnet, characterized in that: The preparation method comprises: placing a NdFeB magnet in the electroplating solution of any one of claims 3 to 6 for electroplating to obtain a NdFeB magnet containing a nickel-cobalt-phosphorus-molybdenum alloy coating.

8. The preparation method according to claim 7, characterized in that: The temperature of the electroplating solution in the electroplating is 45-60°C; Preferably, the pH of the plating solution in the electroplating is 4.0 to 6.5; Preferably, the stirring speed in the electroplating solution during the electroplating is 300-400 r / min; Preferably, the cathode current density in the electroplating is 0.8 to 1.4 A·dm -2 .

9. A neodymium iron boron magnet, characterized in that: The NdFeB magnet comprises the nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet according to claim 1 or 2; or the method for preparing the NdFeB magnet comprises the method for preparing the nickel-cobalt-phosphorus-molybdenum alloy coating of the NdFeB magnet according to claim 7 or 8; Preferably, the NdFeB magnet comprises a magnet body and a coating located on the surface of the magnet body; Preferably, the coating comprises a nickel-cobalt-phosphorus-molybdenum alloy coating; Preferably, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 10 μm; Optionally, when the coating contains only a nickel-cobalt-phosphorus-molybdenum alloy coating, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 6 to 10 μm; or, when the coating further includes a second coating, the thickness of the nickel-cobalt-phosphorus-molybdenum alloy coating is 3 to 5 μm; Preferably, the second coating layer comprises any one of an epoxy film layer, a physical deposition film layer, a nickel-plated layer or a nickel-containing alloy-plated layer, or a combination of at least two thereof.

10. Use of the NdFeB magnet according to claim 9 in the fields of wind power, motors or smart consumer electronics.